SPATIAL-TEMPORAL VARIATION OF GROUNDWATER RECHARGE FROM PRECIPITATION IN THE STONY ATHI SUB-CATCHMENT, KENYA - Mathenge, Morris W.; Gathuru, Dr. Gladys M.; Kitur, Dr. Esther L. (International Journal of Environmental Sciences, 2020)
Purpose: Groundwater recharge is an important process for sustainable groundwater development and its quantification is a prerequisite for efficient management of groundwater resources. The purpose of this study was to evaluate the scale and spatial-temporal variation of groundwater recharge from precipitation in the semi-arid Stony Athi sub-catchment. Methodology: A descriptive case study approach was used for the evaluation. WetSpass-M, a GIS physically based, spatially distributed watershed model was applied. The model integrates biophysical and climatic characteristics of a watershed to simulate the long term mean groundwater recharge. Grid maps of the sub-catchment characteristics were prepared from primary and secondary data using ArcMap. The model was applied for four periods, namely, 1984, 1995, 2005 and 2017. Besides the average groundwater recharge, other outputs of the model include surface run-off and actual evapotranspiration. The study was carried out between January and December 2018. Findings: Land cover in the Stony Athi sub-catchment is comprised of built-up area, agricultural land, grassland, shrub-land, mixed forest and bare land. Topography ranges from 1493 m to 2,082 m above sea level with a slope of between 0% and 30%. Soil types include sandy loam, loam, sandy clay loam, sandy loam and clay. The mean annual precipitation is about 634 mm while the potential evapotranspiration is about 1,490 mm. Annual temperature averages 19.0°C with a mean maximum of 25°C and a mean minimum of 12.7°C. The results of the simulation indicated that the long-term temporal and spatial average annual rainfall of 634 mm is distributed as 88 mm (14%) recharge, 77 mm (12%) surface runoff while 475 mm (75%) is lost through evapotranspiration. Unique contribution to theory, practice and policy: This study demonstrate the importance of physically-based spatially-distributed hydrological models in estimating the water balance. The study provides a theoretical basis for scientific, rational resource allocation and utilization as well as creating awareness of the need to enhance groundwater governance. Results from this study can be used as an input for building an integrated groundwater modelling and for evaluation of potential sites for managed artificial recharge through harvesting runoff to improve groundwater storage.